2020
DOI: 10.1177/2473011420907072
|View full text |Cite
|
Sign up to set email alerts
|

Talar Osteonecrosis After Subchondroplasty for Acute Lateral Ligament Injuries: Case Series

Abstract: Talar osteonecrosis is a well-described phenomenon following talar neck fracture, but is a rarely described complication after procedures about the foot and ankle. Here we describe the clinical course of 5 cases of talar osteonecrosis following injection of calcium phosphate into the talus (subchondroplasty) with or without acute lateral ligament repair after acute lateral ankle ligament injuries performed at an outside institution. Practitioners should be aware of this potentially devastating complication. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We have read with much interest the comments regarding our manuscript written in the discussion section of "Talar Osteonecrosis After Subchondroplasty for Acute Lateral Ligament Injuries: Case Series" and we find that some clarification will be effective at elucidating some concerns. 1,2 The authors state that we reported no complications; however, we did have a complication, which was described in the Results section. This was a 46-year-old obese woman that approximately 5 weeks after her procedure was discovered to have a stress fracture of the talar neck at the calcium-bone interface.…”
Section: Dear Editormentioning
confidence: 65%
“…We have read with much interest the comments regarding our manuscript written in the discussion section of "Talar Osteonecrosis After Subchondroplasty for Acute Lateral Ligament Injuries: Case Series" and we find that some clarification will be effective at elucidating some concerns. 1,2 The authors state that we reported no complications; however, we did have a complication, which was described in the Results section. This was a 46-year-old obese woman that approximately 5 weeks after her procedure was discovered to have a stress fracture of the talar neck at the calcium-bone interface.…”
Section: Dear Editormentioning
confidence: 65%
“…Calcium phosphate injected at a certain volume and for the proper indications may be a therapeutic tool in the foot and ankle surgeon’s armamentarium. However, in addition to our own study 2 and the talar neck fracture described above, 1 another case series was reported at a third institution with findings of talar osteonecrosis in 4 patients. 3 We therefore believe that randomized clinical trials are warranted in the talus by those using this product prior to generalized use by the foot and ankle community.…”
mentioning
confidence: 58%